Unmanned aerial vehicles: A review - Asif Ali Laghari; Awais Khan Jumani; Rashid Ali Laghari; Haque Nawaz (Cognitive Robotics, 2023)
The lightweight Unmanned Aerial Vehicle (UAV) flight activities are constrained, particularly in the UAV range or activity span and perseverance, by the strategic correspondence link capabilities. This paper tends to the different overlap issue of trading off a set of mission prerequisites, the UAV execution parameters, and strategic credibility; thus compromising between the communication load characterized by a crucial, communication link transmitting power necessities, power accessibility onboard UAV as a weight-restricted parameter, and the UAV security.